KEKUASAAN POLITIK MENURUT PEMIKIRAN BUYA HAMKA - zona, ikram ari (UIN Sumatera Utara, 2024)
AbstractThis research aims to analyze Buya Hamka's views on political power and how these views are reflected from the Islamic perspective which is the basis of his thinking. The research method used is a descriptive-analytical method with a qualitative approach. Data was obtained through literature study, by examining various writings and thoughts of Buya Hamka that were relevant to the research theme. The results of the analysis show that in Buya Hamka's view, political power must be exercised by paying attention to Islamic moral and ethical values. For him, political power is a trust that must be accounted for before Allah SWT and is faced with the public interest and welfare of society. Buya Hamka emphasized that political power must be used for the common good, not for personal interests or certain groups. In the Islamic perspective he adheres to, Buya Hamka emphasizes the principles of justice, truth and balance in the management of political power. He also emphasized the importance of openness, accountability and public participation in the political process. These thoughts made an important contribution to the formation of Islamic political insight in Indonesia. In conclusion, Buya Hamka's thoughts on political power emphasize the importance of applying Islamic values in carrying out political affairs. This view is relevant to consider in the context of Indonesia's current political dynamics, where Islamic values are often an integral part of the political and social order of society.Keywords: Power, Politics, Buya Hamka